Rasch Analysis and Differential Item Functioning of Work-Related Flow Inventory (WOLF): A Study on the Hotel Industry in Sarawak - Mark, Kasa; Stephen, Donal; Zaiton, Hassan (De La Salle University, 2019)
This study has examined the psychometric properties of Work-Related Flow Inventory (WOLF) that examines the flow experience at work by measuring employees’ absorption, enjoyment, and intrinsic motivation (Bakker, 2005, 2008). Absorption is defined as a state of total concentration while immersed in the work. As for enjoyment, it is referred to as a positive judgment on the matter of the quality of work. Lastly, intrinsic motivation is defined as the willingness to exhibit certain behaviors that stemmed from inherent satisfactions rather than separable consequences (Ryan & Deci, 2000). The term flow was introduced by Csikszentmihalyi (1990) who defined it as “the state in which people are very intensely immersed in an activity that nothing else seems to matter; the experience itself is so enjoyable whereby people will do it even at a great cost, for the sheer sake of doing it” (Csikszentmihalyi, 2003, p. 4). It was recognized that the notion of flow has a positive relationship with the productivity of an organization. The notion of flow is attributed to the willingness to seek constant optimal experiences that could lead to more willingness to invest time and effort in a task voluntarily (Seligman, Csikszentmihalyi, Fredrikson, Wateman, & Emmons, 2011)